1999
DOI: 10.1002/(sici)1521-3927(19990501)20:5<274::aid-marc274>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Sm(II) compounds as ring-opening polymerization initiators for lactones

Abstract: SUMMARY: Successful room temperature ring-opening polymerization (ROP) of e-caprolactone and d-valerolactone has been carried out using SmX 2 (X = I, Br, and cyclopentadienyl (Cp)) catalysts. SmI 2 in the presence of metallic Sm was found to have enhanced reactivity as room temperature ROP initiator for lactones as compared to pure SmI 2 . SmBr 2 and SmCp 2 showed increased reactivity compared with the Sm/SmI 2 system due to their higher reductive power. The catalyst concentration and time of polymerization sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
2
11
0
1
Order By: Relevance
“…In our previous report, both Sm(II) complexes [SmI 2 and Sm(PPh 2 ) 2 ] were examined to compare their relative activity for the ROP of CL 15. Just as reported by Evans and Katsumata,19 SmI 2 showed no reactivity for the polymerization at the ambient temperature over 6 h. However, polymerization occurred in THF at the reflux temperature or, in the case of a low monomer/Sm ratio, with a longer reaction period 20. On the other hand, we found that Sm(PPh 2 ) 2 could initiate the ROP of CL effectively at room temperature, giving polyesters with a higher molecular weight.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…In our previous report, both Sm(II) complexes [SmI 2 and Sm(PPh 2 ) 2 ] were examined to compare their relative activity for the ROP of CL 15. Just as reported by Evans and Katsumata,19 SmI 2 showed no reactivity for the polymerization at the ambient temperature over 6 h. However, polymerization occurred in THF at the reflux temperature or, in the case of a low monomer/Sm ratio, with a longer reaction period 20. On the other hand, we found that Sm(PPh 2 ) 2 could initiate the ROP of CL effectively at room temperature, giving polyesters with a higher molecular weight.…”
Section: Resultssupporting
confidence: 77%
“…This decrease in the molecular weight was probably due to transesterification reactions. Similar behavior was observed for the ROP of cyclic esters by other lanthanide catalysts 20, 22…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…SmI 2 initiates ROP of CL only at elevated temperatures or at room temperature in the presence of Sm metal. 26,27 The living character of the polymer chain ends was investigated by block copolymerization CL with VL using 1 (1/CL, 1:150). First, CL was polymerized using 1 as initiator.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] A less known route to the formation of poly(caprolactone), first shown by Bailey et al 8 and later followed by some others, 9,10 is by radical ringopening polymerization of 2-methylene-1,3-dioxepane (MDO). 2-methylene-1,3-dioxepane is an interesting cyclic ketene acetal monomer giving poly("-caprolactone) (PCL), on the radical-ring-opening homopolymerization (RROP) and can introduce ester groups onto the vinyl polymer backbones during copolymerizations with vinyl monomers.…”
mentioning
confidence: 97%